EFEKTIVITAS GAME-BASED LEARNING BERBASIS GENIALLY TERHADAP MOTIVASI BELAJAR PAI PESERTA DIDIK DI SMPN 5 SURABAYA - M. Nasihuddin; Ismail Anas (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2025)
The low level of students’ learning motivation in Islamic Religious Education (IRE) remains a challenge, particularly due to the limited use of varied and interactive learning media. This study aims to examine the effectiveness of implementing game-based learning media in the form of a snakes and ladders game developed using the Genially platform in improving students’ learning motivation at a public junior high school in Surabaya. This research employed a quantitative approach with a quasi-experimental control group design. The sample consisted of 60 eighth-grade students selected through purposive sampling. Data were collected through observation and questionnaires and analyzed using descriptive analysis and a t-test. The results indicate a significant increase in students’ learning motivation following the implementation of Genially-based game-based learning media. The learning motivation score improved from the “strong” category to the “very strong” category, and the t-test results showed a significance value of 0.00 (< 0.05). These findings demonstrate that Genially-based game-based learning media are effective in enhancing students’ learning motivation in Islamic Religious Education. This study contributes to the development of innovative and digitally based learning media for Islamic Religious Education.